Biomechanical effects of transforaminal endoscopic lumbar discectomy combined with spinal dynamic stabilization system use on adjacent segments: a finite element analysis - Rongbin Chen; Yan Dou; Canjin Peng; Yihao Liang; Jianquan Chen; Shunping Li; Zhaotian Wu; Yong Li (BMC Musculoskeletal Disorders)
Abstract Objective To assess the biomechanical effect of transforaminal endoscopic lumbar discectomy combined with spinal dynamic stabilization system (TELD-SDSS) on the adjacent segments using three-dimensional finite element (3D-FE) analysis, providing reference data for the optimization of surgical approaches for giant lumbar disc herniation (GLDH). Methods A 3D-FE model of L3–S1 was constructed based on imaging data and validated against well-established in-vitro biomechanical data. Surgical FE models representing TELD, TELD-SDSS, and posterior lumbar interbody fusion (PLIF) were reconstructed. The risk of adjacent segment degeneration (ASD) was evaluated by comparing adjacent-segment biomechanical parameters under various loading directions using hybrid testing methods. Results Compared with the FE model, the PLIF model showed the largest increases in adjacent-segment range of motion, intradiscal pressure, endplate Von Mises stress, and annulus fibrosus shear stress under flexion, extension, lateral bending, and rotational loading. The TELD-SDSS model showed lesser increases, and results for the TELD models did not differ significantly. Conclusions The study findings suggest that TELD with limited foraminoplasty and large annuloplasty has no significant impact on the occurrence of ASD. Although TELD-SDSS application alters the biomechanical environment of the adjacent segments, it has potential biomechanical advantages over PLIF in the mitigation of ASD occurrence.